2013
DOI: 10.1371/journal.pone.0054371
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Impact of Subsidizing Artemisinin-Based Combination Therapies (ACTs) in the Retail Sector – Results from Focus Group Discussions in Rural Kenya

Abstract: BackgroundThere is considerable interest in the potential of private sector subsidies to increase availability and affordability of artemisinin-based combination therapies (ACTs) for malaria treatment. A cluster randomized trial of such subsidies was conducted in 3 districts in Kenya, comprising provision of subsidized packs of paediatric ACT to retail outlets, training of retail staff, and community awareness activities. The results demonstrated a substantial increase in ACT availability and coverage, though … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 28 publications
(41 reference statements)
0
13
0
Order By: Relevance
“…The year 2010 was the first year that the Affordable Medicines Facility-malaria program to subsidize ACT at private retailers was implemented with the intention of reducing the cost of ACT to 40 KES (equivalent to $0.50 at the time) around the country [ 26 , 27 ]. However, the discrepancy between the cost of the drug and the full cost of a hospital visit for malaria care was large and posed a significant burden to the affected population.…”
Section: Discussionmentioning
confidence: 99%
“…The year 2010 was the first year that the Affordable Medicines Facility-malaria program to subsidize ACT at private retailers was implemented with the intention of reducing the cost of ACT to 40 KES (equivalent to $0.50 at the time) around the country [ 26 , 27 ]. However, the discrepancy between the cost of the drug and the full cost of a hospital visit for malaria care was large and posed a significant burden to the affected population.…”
Section: Discussionmentioning
confidence: 99%
“…Our study found several shop workers who described scenarios in which they may not trust test results, potentially leading to an underutilization of the tests. A recent study by Kedenge and colleagues [31] evaluating the effectiveness of a subsidized antimalarial intervention in Kenyan retail shops found that shop workers did not consistently perform certain components of the intervention such as provision of advice, stating that they were too busy with other customers. This trend among for-profit shop workers may limit their ability to accurately and consistently administer rapid tests to their clients.…”
Section: Discussionmentioning
confidence: 99%
“…Overall the private sector subsidy programmes of ACTs seem to have been successful in increasing availability of effective antimalarial treatment in private outlets, but in some contexts this availability was limited if implementation was not supported by complementary interventions like community awareness campaigns ( Yeung et al. 2011 ; Kedenge et al. 2013 ; O’Meara et al.…”
Section: Resultsmentioning
confidence: 99%
“…The private sector subsidy programmes of ACTs have started to open the road to subsidization of commodities through existing supply channels with the goal of reaching a target population ( Patouillard et al. 2010 ; Kedenge et al. 2013 ).…”
Section: Resultsmentioning
confidence: 99%